ACR–ASTRO Practice Parameter for the Performance of Stereotactic Body Radiation Therapy. (August 2020) - Chao, Samuel T.; Dad, Luqman K.; Dawson, Laura A.; Desai, Neil B.; Pacella, Matthew; Rengan, Ramesh; Xiao, Ying; Yenice, Kamil M.; Rosenthal, Seth A.; Hartford, Alan
Abstract : Aim/Objectives/Background: To standardize the practice of stereotactic body radiation therapy (SBRT), the American College of Radiology (ACR) and the American Society for Radiation Oncology (ASTRO) cooperatively developed the practice parameter for SBRT. SBRT is a treatment technique that delivers radiation dose to a well-defined extracranial target in 5 fractions or less and usually employs a higher dose per fraction than used in conventional radiation. Methods: The ACR–ASTRO Practice Parameter for the Performance of Stereotactic Body Radiation Therapy was revised according to the process described on the ACR website ("The Process for Developing ACR Practice Parameters and Technical Standards, " www.acr.org/ClinicalResources/Practice-Parameters-and-Technical-Standards ) by the Committee on Practice Parameters of the ACR Commission on Radiation Oncology in collaboration with the ASTRO. Both societies then reviewed and approved the document. Results: Given the complexities of SBRT, a separate document was created to develop a technical standard for the medical physics of SBRT (ACR–AAPM Technical Standard for Medical Physics Performance Monitoring of Stereotactic Body Radiation Therapy). Workflow, qualifications and responsibilities of personnel, specifications, documentation, quality control/safety/improvement, simulation/treatment, and follow-up were addressed in this practice parameter. Conclusions: This practice parameter assists practitioners in providing safe and appropriate SBRT treatment and care for patients when clinically indicated. As technologies and techniques continue to evolve, this document will be reviewed, revised and renewed accordingly to a 5 year or sooner timeline specified by the ACR.